AN ANALYSIS OF ONLINE LEARNING SPEAKING AT INTENSIVE ENGLISH CLASS DURING COVID-19 - Nurwahyuni, Rizki; Asi, Natalina; Luardini, Maria Arina (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2021)
The objective of the study aims to analyze the implementation of online learning speaking and the advantages of synchronous and asynchronous learning modes at Intensive English class at Languages Development Unit in UIN Antasari Banjarmasin. The research applied qualitative approach. The participant of this research was the second group of Intensive English Class. The data was collected from observation, interview and questionnaire. To analyze the data, the researcher used descriptive analysis. The results showed the implementation of online learning at Intensive English class during Covid-19 has been quite effective even though it takes a lot of effort to adapt for both the instructor and the students. The advantages from online learning such as more flexible to learn, train the student become more independent in learning etc.